TECTONIC STRAIN IN SUMATRAN BASED ON CONTINUOUS OBSERVATIONS OF SUMATRAN GPS ARRAY (SUGAR) 2007-2008 - (NIM 15106011); Pembimbing: Dr. Irwan Meilano, ST, M.Sc dan Irwan Gumilar, ST, M.Si., RINO
Sumatran is located near the companion of the Indo-Australian Plate and Eurasian Plate. When the Indo-Australian Plate moving down the Eurasian Plate, the field of inter-plate contact occurs so that the strain accumulates. Strain that has passed the limit of elasticity will be released as an earthquake. GPS observations carried out to study the velocity vector of displacements and tectonic strain variations in surface. The results from data processing indicate that vector displacements in Sumatran leads to northeastern which indicate inter-seismic and southwest which indicate post-seismic. Strain distribution in the form of extension which indicate post-seismic, spread dominant in Aceh 2004 earthquake, Nias 2005 earthquake, Bengkulu 12 September 2007 earthquake and the Mentawai Islands 13 September 2007 earthquake. Strain in the form of compression showed that Sumatran still influenced by the inter-seismic.